GRAMMATICAL ERROR ANALISYS IN THAI STUDENTS’ ENGLISH WRITING AND SPEAKING AT UIN ALAUDDIN MAKASSAR - Anci Bte Syarifuddin (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aims at finding out the types of grammatical errors and the causes of errors in Thai students‟ English writing and speaking. The research employed descriptive qualitative method. The sample consisted of 9 Thai students. The data were collected by using observing, recording and interviewing the students which was analysed through open coding, axial coding and selective coding. The research result indicated that there are some types and causes of errors found in Thai students‟ English writing and speaking. There are about 85 errors in writing. Some types of error also appeared in students‟ speaking. There are about 39 errors in speaking.There are several causes of error found in Thai students‟ English writing and speaking. Interference of native language is the most influencing factors in Thai students‟ writing and speaking, the second is overgeneralization, the third is performance errors, and the last is students‟ educational and economic background.KEY WORDS